2019
DOI: 10.1016/j.fertnstert.2018.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Circulating antimüllerian hormone and steroid hormone levels remain high in pregnant women with polycystic ovary syndrome at term

Abstract: Objective: To investigate plasma antim€ ullerian hormone (AMH) concentration and its relation to steroid hormone levels in pregnant women with polycystic ovary syndrome (PCOS) and controls at term. Design: Case-control study. Setting: University-affiliated hospital. Patient(s): A total of 74 pregnant women at term: 25 women with PCOS (aged 31.6 AE 3.9 years [mean AE standard deviation], body mass index 24.0 AE 3.9 kg/m2, mean gestational length 279 AE 9 days) and 49 controls (aged 31.7 AE 3.3 years, body mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 47 publications
3
41
0
2
Order By: Relevance
“…Women with PCOS have higher testosterone levels during pregnancy compared with women without PCOS. This finding is in line with previous studies in pregnant women with PCOS, in which high testosterone levels also in late pregnancy have been noted (Glintborg et al, 2018;Detti et al, 2019;Piltonen et al, 2019). In pregnancy, maternal testosterone levels depend mainly on the feto-placental unit.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Women with PCOS have higher testosterone levels during pregnancy compared with women without PCOS. This finding is in line with previous studies in pregnant women with PCOS, in which high testosterone levels also in late pregnancy have been noted (Glintborg et al, 2018;Detti et al, 2019;Piltonen et al, 2019). In pregnancy, maternal testosterone levels depend mainly on the feto-placental unit.…”
Section: Discussionsupporting
confidence: 92%
“…We and other investigators have previously demonstrated that women with PCOS have higher AMH levels during pregnancy (Detti et al,. 2019;Piltonen et al, 2019;Valdimarsdottir et al, 2019). As AMH is produced by the antral follicles in the ovary and by the placenta (Novembri et al, 2015), and as AMH is correlated with testosterone levels (Detti et al, 2019;Piltonen et al, 2019;Valdimarsdottir et al, 2019), it may be speculated that the ovaries continue contributing to the overall testosterone synthesis in pregnant women with PCOS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies suggest that AMH may be involved in this phenomenon. Circulating AMH levels are higher in pregnant women with PCOS compared to those with normal fertility (66,67) and are correlated with androgen levels (67). These results therefore suggest that AMH at relatively high concentration during pregnancy could itself be the cause of prenatal programming of PCOS.…”
Section: Is Excess Amh Involved In the Trans-generational Transmissiomentioning
confidence: 78%
“…It has been shown that patients with HOXA10 mutations had uterine defects ranging from septate uterus to a didelphys uterus indicative of MD fusion defects. (21)(22)(23) In a review, it was clearly shown that intrauterine hyper exposure to testosterone influences the expressing genes. 23There may be other mechanisms that are responsible for increased intrauterine hyper androgens linked with intrauterine AMH function.…”
Section: Discussionmentioning
confidence: 99%